The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1960
DOI: 10.1042/bj0750082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biochemistry of urea synthesis. 3. Activities of urea cycle enzymes in various higher and lower vertebrates

Abstract: 4. The ratio of potassium to sodium decreased significantly with advancing age in kidney and heart tissue. 5. Nine tissues were analysed from a further five LK and five HK aged ewes. The skeletal muscle, liver, spleen and kidney (expressed on a fatand blood-free basis) of the aged HK ewes tended to have higher concentrations of potassium (1.5, 2*2, 3-6 and 1-9% respectively) and lower concentrations of sodium (10-7, 12 3, 9 2 and 4 8 % respectively) than those of the aged LK ewes. 6. Rumen epithelium from LK s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(83 citation statements)
references
References 9 publications
1
81
1
Order By: Relevance
“…SCHIMKE [32] has shown that the enzymes of urea biosynthesis rise in a coordinate manner when increasing percentages of dietary proteins were fed to rats. BROWN et al [6] showed the simultaneous appearance of enzymes of the urea pathway during amphibian metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…SCHIMKE [32] has shown that the enzymes of urea biosynthesis rise in a coordinate manner when increasing percentages of dietary proteins were fed to rats. BROWN et al [6] showed the simultaneous appearance of enzymes of the urea pathway during amphibian metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…In aqueous solution, ammonia exists in equilibrium between its gaseous (NH 3 ) and ionic (NH 4 ϩ ) forms, and the high solubility of NH 3 coupled with a favorable partial pressure gradient was thought to permit ready diffusion across the gills. "Acid trapping", acidification of the gill boundary layer via hydration of CO 2 or direct excretion of protons, results in the conversion of excreted NH 3 into NH 4 ϩ , thereby maintaining a favorable gradient for NH 3 movement (43,55,59).…”
mentioning
confidence: 99%
“…Blood ammonia was determined as described by Gips and WilkensAlberts [8]. The methods of Brown and Cohen [3] were used for the quantitative assay of urea cycle enzymes. Amniotic cells were obtained by transabdominal amniocentesis after localization of the placenta by echoscopy in the 20th week of pregnancy, after one failure at 16 weeks.…”
Section: Methodsmentioning
confidence: 99%